Effect of seasonal variations on electrophoretic pattern of serum proteins and some biochemical indices in Ossimi ewes and their neonatal lambs - G. A. E. Mohamed; H. M. A. Monzaly (Bulgarian Journal of Veterinary Medicine, 2023)
This study aimed to observe the impact of seasonal variations on the behaviour of serum proteins electrophoretic patterns by the Hellabio Agarose Gels and the changes of some metabolic indices in Ossimi ewes and their lambs (1530 days postpartum). Serum samples from 20 ewes and their lambs during each season (summer and winter) were used in this study. Temperature-humidity index (THI) in winter was 72 (comfort), but a severe stress was shown in July, when the THI exceeded 90. Blood albumin decreased by 7.31% and 9.92% in summer, but the contrary was shown for α-globulins in ewes and lambs:α1-globulins increased by 52.94 % and 22.22 %, α2-globulins by 27.85 % and 93.02 % and albumin/globulin (A/G) ratio by 13.11% and 20% in summer, compared with winter. The val-ues of β-globulins and γ-globulins did not differ between seasons. Ewes had higher values for protein fractions than lambs, but the reverse was true for A/G ratio. Summer serum glucose increased by 16.16% and 13.42%, urea by 16.16% and 25.78% and creatinine by 21.49% and 26.63%, whereas summer calcium (Ca) decreased by 6.81% and 5.18% and inorganic phosphorus (P) by 12.68% and 13.89% in ewes and their lambs respectively compared with winter. Lambs had higher values of se-rum glucose, Ca and P than their mothers, however the opposite was true for urea and creatinine. The presented results indicate that hot environment in summer season causes changes in serum protein electrophoretic patterns and metabolic indices in Ossimi ewes and their newborn lambs, which indicates an adaptive performance of these animals to seasonal variations and heat stress.